Cuentos, capturando la inocencia y crueldad de los cuentos de hadas : Sonya Hurtado - Algibez, Laura (2017)
This communication is a proposal to study in deep the photographic work ‘Tales’ as a digital art by the artist Sonya Hurtado. This would take us to a visual exploration and analysis of the imaginary world of childhood. The approach to the study of Hurtado’s work would be focusing in two points: first it will consider the context of fairy tales and children’s stories’ narratives and how they are transformed into a visual language and the second to focus in the photographic process to create a unique visual narrative that allows her to share and present to the public in an intelligent and sensible way the popular fairytales